2009
DOI: 10.1038/npp.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Increase of Alcohol-Seeking Evoked by Neuropeptide S: an Effect Mediated by the Hypothalamic Hypocretin System

Abstract: The association of ethanol's reinforcing effects with specific environmental stimuli is thought to be a critical factor for relapse risk in alcoholism. This study examined in rats the effects of a newly deorphanized neuropeptide receptor and its cognate ligand, Neuropeptide S (NPS), on ethanol consumption and reinstatement of ethanol-seeking by environmental cues previously associated with ethanol availability. In the self-administration experiments, the stable response rates observed for ethanol reinforcement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 30 publications
(41 reference statements)
7
102
1
5
Order By: Relevance
“…The genetic make up of this selectively bred alcohol-preferring rat strain is not completely clear, but could presumably include effects on NPS, NPSR, or effector systems downstream of the receptor. In line with Badia-Elder's data in EtOH non-preferring rats, Cannella et al (2009) showed that NPS had no effect on EtOH consumption in wistar rats. Thus, genetic factors clearly influence the effect of NPS both on reward and EtOH consumption.…”
Section: Discussionsupporting
confidence: 75%
“…The genetic make up of this selectively bred alcohol-preferring rat strain is not completely clear, but could presumably include effects on NPS, NPSR, or effector systems downstream of the receptor. In line with Badia-Elder's data in EtOH non-preferring rats, Cannella et al (2009) showed that NPS had no effect on EtOH consumption in wistar rats. Thus, genetic factors clearly influence the effect of NPS both on reward and EtOH consumption.…”
Section: Discussionsupporting
confidence: 75%
“…Given that in postdependent rats protracted abstinence is associated with increased HPA axis activity and higher peripheral corticosteroids levels (Rasmussen et al, 2000;Zorrilla et al, 2001), we may speculate that facilitation of NPS function in the PaV may contribute to this hormonal dysregulation. Previous studies conducted in our laboratory have also shown that central activation of NPS receptors facilitates relapse to alcohol seeking; thus, considering that postdependent rats are more inclined to relapse, one could speculate that higher NPS neurotransmission levels following alcohol intoxication history may contribute to exacerbate this behavior (Cannella et al, 2009;Liu and Weiss, 2002). At present, it is unclear how to reconcile the NPS anxiolytic-like profile with its ability to facilitate reinstatement of alcohol seeking as previously described in our laboratory (Cannella et al, 2009).…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies conducted in our laboratory have also shown that central activation of NPS receptors facilitates relapse to alcohol seeking; thus, considering that postdependent rats are more inclined to relapse, one could speculate that higher NPS neurotransmission levels following alcohol intoxication history may contribute to exacerbate this behavior (Cannella et al, 2009;Liu and Weiss, 2002). At present, it is unclear how to reconcile the NPS anxiolytic-like profile with its ability to facilitate reinstatement of alcohol seeking as previously described in our laboratory (Cannella et al, 2009). One would, however, speculate that neurocircuitary associated with relapse behavior and anxiety could be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICV injection of NPS has also been shown to stimulate hypothalamic-pituitary-adrenal axis (HPA) activity, enhancing plasma adrenocorticotropic hormone (ACTH) and corticosterone levels (3). Our group has recently found that intra-LH injections of NPS facilitate conditioned reinstatement of alcohol seeking (4). In addition, Pañeda and coworkers reported that ICV NPS itself increased relapse-like behavior in mice previously trained to self-administer cocaine.…”
mentioning
confidence: 95%